Decreased serum adiponectin levels in hypertensive patients - Özkan, Yusuf; Koca, Süleyman Serdar; Gencer, Vedat; Özalp, Göksel; Dönder, Emir (Turkiye Klinikleri, 2005)
Objective: Atherosclerotic vascular diseases are among the leading causes of mortality and morbidity in Western societies. Hypertension (HT) is a major changeable risk factor in atherosclerosis. Adiponectin, which is secreted from adipose tissue, is an antiinflammatory cytokine with a regressive and protective effect on atherosclerosis. In the present study, we examined serum adiponectin levels in essential hypertension. Material and Methods: Included were 38 essential hypertension patients who presented in the Firat Medical Center General Internal Diseases Polyclinic between January and June 2004, as well as 10 healthy individuals. Oral consent was obtained, physical examinations were conducted and demographical characteristics were recorded. In addition to routine blood chemistry, insulin, C-peptide and adiponectin levels were noted. Adiponectin was examined using the ELISA method. The Mann Whitney U test was used in the evaluation of data. Results: The mean adiponectin level was 18.8 ± 6.8 ?g/mL in the healthy individuals and 5.8 ± 2.1 ?g/mL in the HT group, the difference therein being statistically significant (p< 0.05). Fasting blood sugar, basal insulin, HOMA IR, total cholesterol, triglyceride, and LDL-cholesterol levels in the hypertensive individuals were significantly higher than those in the control group. The mean adiponectin level was 6.7 ± 2.3 ?g/mL in non-obese hypertensive cases and 5.1 ± 1.7 ?g/mL in obese hypertensive cases; the difference between the two was statistically significant (p< 0.05). Adiponectin levels in hypertensive patients who did not have a familial diabetes history were significantly lower than those in hypertensive patients with such a history (p< 0.05). Adiponectin levels were also found to be lower in males, smokers and less active hypertensive patients, but the difference was not statistically significant. Conclusion: Serum levels of adiponectin, an anti-inflammatory cytokine, decrease in the presence of HT. When obesity, sedentary life-style, smoking, diabetes and a familial history of cardiovascular diseases accompany hypertension, serum adiponectin levels show a further decrease. Copyright © 2005 by Türkiye Klinikleri.
Hipertansif olgularda azalmiş serum adiponektin düzeyleri
Keywords: Adiponectin; Atherosclerosis; Hypertension